2022
DOI: 10.1155/2022/2863379
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Biomechanical Analysis of Different Internal Fixation Combined with Different Bone Grafting for Unstable Thoracolumbar Fractures in the Elderly

Abstract: This research was developed to accurately evaluate the unstable fractures of thoracolumbar before and after surgery and discuss the treatment timing and methods. Three-dimensional (3D) finite element method was adopted to construct the T12-L5 segment model of human body. The efficiency of percutaneous kyphoplasty (PKP) and percutaneous vertebroplasty (PVP), two commonly used internal fixation procedures, was retrospectively compared. A total of 150 patients with chest fracture who received PKP or PVP surgery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…According to previous studies, most screw fractures are mainly located in the middle and head of the screws, which may be related to different internal fixation methods. [10][11][12] With the progress of medical technologies, the material and shape of lumbar internal fixation system have been upgraded and improved, but screw fracture still occurs. 13,14 Therefore, how to ensure the safety and stability of pedicle screws and connecting rods has become a key issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, most screw fractures are mainly located in the middle and head of the screws, which may be related to different internal fixation methods. [10][11][12] With the progress of medical technologies, the material and shape of lumbar internal fixation system have been upgraded and improved, but screw fracture still occurs. 13,14 Therefore, how to ensure the safety and stability of pedicle screws and connecting rods has become a key issue.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most serious consequences is the fracture of the screw, which is mainly caused by the torsion or bending of the body. According to previous studies, most screw fractures are mainly located in the middle and head of the screws, which may be related to different internal fixation methods 10–12 . With the progress of medical technologies, the material and shape of lumbar internal fixation system have been upgraded and improved, but screw fracture still occurs 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%